2014
DOI: 10.1109/tps.2013.2288699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultraviolet Irradiation and Atomic Oxygen Erosion on Total Electron Emission Yield of Polyimide

Abstract: Polymers used on low earth orbit (LEO) spacecraft surface suffer from an ultraviolet (UV) irradiation and orbital atomic oxygen (AO) erosion. These degradations may change the total electron emission yield (TEEY) of the materials and ultimately result in unexpected surface charging. In this paper, we chose polyimide (PI) film, a thermal control material, and carried out two types of ground-based degradation. The degradation methods were UV irradiation with five different equivalent solar hours, and AO erosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Thus, the un-bonded electron in the free radical is considered to enhance the generation of the secondary electron and photoelectron. Our previous research on the ultraviolet irradiation on total electron emission yield proved to be the same tendency 17) . However, the PEY of electron irradiation polyimide film decreased with the rising of electron irradiation dose, which infers, there exists other degradation effects besides of the generation of free radicals.…”
Section: Discussion and Analysismentioning
confidence: 63%
“…Thus, the un-bonded electron in the free radical is considered to enhance the generation of the secondary electron and photoelectron. Our previous research on the ultraviolet irradiation on total electron emission yield proved to be the same tendency 17) . However, the PEY of electron irradiation polyimide film decreased with the rising of electron irradiation dose, which infers, there exists other degradation effects besides of the generation of free radicals.…”
Section: Discussion and Analysismentioning
confidence: 63%
“…Exposure of PI to UV irradiation results in the formation of a high concentration of radicals as confirmed by EPR studies [112][113][114][115]. These radicals originate from a broken C-N bond in the imide group and the C-O bond of the ether of PI [116]. Results of spectroscopic ellipsometry of UV-exposed PI films suggested that the UV generated radicals are situated near the surface of the film, with~500 nm depth of damaged layer [117].…”
Section: Changes In Chemical Propertiesmentioning
confidence: 78%
“…This theory is supported by a study on the effects of ultraviolet irradiation on LEO spacecraft surfaces. It was found that UV photons, the radiation responsible for the photoemission of electrons from the sensor surfaces, normally travel up to a depth of 0.1 μm in material (Wu et al., 2014). This implies that surface irregularities within the top 0.1 μm of the DAG‐213 coating may play the largest role in the photoemission properties of the EFW sensors.…”
Section: Discussionmentioning
confidence: 99%